A bioactive SBS material for skull repair and its preparation method and application

By covalently connecting aldehyde-modified quaternary ammonium chitosan and fixing polydopamine-modified zeolite imidazole backbone and hydroxyapatite on SBS materials, the infection control and bone of existing skull repair materials is solved The problem of insufficient integration ability significantly improves antibacterial properties and osteogenic differentiation capabilities.

CN116271212BActive Publication Date: 2025-01-10四川大学青岛研究院
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310300781.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-04-11
Filing Date
2023-03-24
Publication Date
2025-01-10
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

The existing skull repair materials have insufficient infection control and osseous integration capabilities, resulting in high infection rate and poor osseous integration after skulloplasty.

Method used

The quaternary ammonium salt chitosan modified by covalently connecting the aldehyde on the SBS substrate, and the polydopamine-modified zeolite imidazole backbone and polydopamine-modified hydroxyapatite are fixed on its surface to form a bioactive SBS material.

Benefits of technology

This material significantly improves antibacterial properties and promotes osteogenic gene expression and mineralization ability, effectively reducing the risk of infection and the probability of poor osteointegration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116271212B_ABST
    Figure CN116271212B_ABST
Patent Text Reader

Abstract

The present invention discloses a bioactive SBS material for skull repair and its preparation method and application. The preparation method is: covalently linking modified quaternary ammonium salt chitosan on an SBS substrate, and then fixing polydopamine-modified zeolite imidazolate framework-8 and polydopamine-modified hydroxyapatite on its surface. The skull shaping material prepared by the present invention has inherent bactericidal properties and osteogenic gene expression and mineralization capabilities, which can effectively solve the problems of poor infection control ability and insufficient bone integration ability of existing skull repair materials such as titanium mesh, polyether ether ester, and polymethyl methacrylate, which makes it have unique advantages as a biological repair material and has good market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of skull biomaterials and tissue engineering, and in particular relates to a bioactive SBS material for skull repair and a preparation method and application thereof. Background Art

[0002] Intracranial resections caused by neurological diseases such as intracranial malignant tumors, traumatic brain injury, large-area cerebral infarction or stroke, and congenital skull malformations are prone to skull defects, which make the brain tissue unprotected. Moreover, if patients do not undergo cranioplasty after craniotomy, they are prone to serious complications such as neurological dysfunction, brain deformation, and fatal cerebrospinal fluid leakage, which seriously affect the patient's life. Therefore, skull repair is usually required after craniectomy, which brings with it the difficulty of skull defect reconstruction.

[0003] Autologous transplant materials mainly include autologous skull and bone flaps from other parts of the human body, which are considered to be the most suitable materials for cranioplasty. However, when bone flaps are removed from the ilium, ribs, sternum and other parts of the human body, it will cause morbidity in the donor area and cause secondary injury problems. In addition, autologous bone is difficult to preserve and has ethical issues after being removed from the body, so bone flaps from the body are not advisable.

[0004] In contrast, heterogeneous synthetic materials as artificial skulls have attracted widespread attention due to their advantages such as short operation time, no donor site morbidity, easy access, good batch consistency and no ethical issues. At present, titanium mesh, hydroxyapatite (HA), alumina ceramics, polymethyl methacrylate (PMMA) and polyetheretherketone (PEEK) are common synthetic skull repair materials. Although these materials have been successfully used in cranioplasty, there are still certain problems in clinical practice. Poor infection control ability and insufficient bone integration ability are their main problems. Other disadvantages, such as high cost, high 3D printing temperature (for PEEK), thermal conductivity (for titanium mesh), brittleness (for HA and alumina ceramics) and exothermic combustion reaction (for PMMA) have also hindered their development to a certain extent.

[0005] At the same time, it is worth noting that there are two major complications after cranioplasty. One is surgical site infection, with an infection rate of up to 33%. Generally speaking, infection is highly correlated with the formation of biofilms. Biofilms are aggregated bacterial groups adhering to wounds or implant surfaces, and their resistance to antibiotics is 10 to 1000 times higher than that of planktonic bacteria. This is the key reason why biofilm infection-related diseases are difficult to treat. Therefore, intrinsic antibacterial properties are essential for implants to prevent infection and control early infection. The second is poor bone integration, which is closely related to the increased risk of displacement. Therefore, there is an urgent need to develop a bioactive SBS cranioplasty material. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the present invention provides a bioactive SBS material for skull repair and a preparation method and application thereof. The SBS material prepared by the present invention has good bactericidal effect and the ability to promote osteogenic gene expression and mineralization, and can effectively solve the problems of poor infection control ability and insufficient bone integration ability of existing skull repair materials.

[0007] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:

[0008] A method for preparing a bioactive SBS material for skull repair comprises: covalently linking aldehyde-modified quaternary ammonium salt chitosan on an SBS (poly(styrene-butadiene-styrene)) substrate, and then fixing polydopamine-modified zeolite imidazolate framework-8 and polydopamine-modified hydroxyapatite on the surface thereof.

[0009] Further, the preparation method of quaternary ammonium salt chitosan is as follows:

[0010] 5 g CS (chitosan) was dissolved in 180 mL deionized water, and then 900 μL acetic acid solution (0.5% v / v) was added dropwise, and stirred at 55°C for 1 h; 5795 μL trimethylammonium glycidyl chloride was added dropwise to the mixture, and reacted at 55°C for 18 h; after the reaction, the solution was centrifuged at 4500 r / min for 20 min, and then the supernatant was filtered and the filtrate was precipitated in an ethanol / acetone mixture (1:1, v / v); finally, the precipitate was dried in a vacuum oven at room temperature for 3 d to obtain QCS (quaternary ammonium chitosan).

[0011] Furthermore, the quaternary ammonium salt chitosan is modified by using natural aldehyde compounds.

[0012] Furthermore, the natural aldehyde compound is protocatechuic aldehyde, perillaldehyde or vanillin, etc., and the modification process thereof is as follows:

[0013] Weigh 0.5 g of QCS and dissolve it in 40 mL of MES solution (pH = 5.5), stir overnight; dissolve 1 g of protocatechuic aldehyde in 30 mL of water / methanol mixture (2:1, v / v), stir at room temperature for 3.5 h, and then add the solution to the above QCS solution; add 250 mg of NaBH 4 Slowly add it to the mixed solution until no bubbles are generated, adjust the pH value of the solution to 5.5, and stir overnight; after the reaction is completed, put the obtained product into a dialysis bag (MWCO 3500) and dialyze it in an acidic aqueous solution (pH 5.0, HCl) for 2 days, and finally freeze-dry to obtain QCSC (quaternary ammonium salt chitosan modified by protocatechuic aldehyde).

[0014] Further, the process of covalently linking the modified quaternary ammonium salt chitosan on the SBS substrate is as follows:

[0015] (1) placing an SBS substrate in a silane coupling agent, and then cleaning the substrate after plasma surface treatment to obtain an SBS-Si substrate;

[0016] (2) The SBS-Si substrate is placed in a protocatechuic aldehyde-modified quaternary ammonium salt chitosan solution and soaked at 50-70° C. for 30-50 hours.

[0017] Furthermore, the silane coupling agent is trimethoxysilane (GPTMS) or KH560.

[0018] Furthermore, the concentration of the protocatechuic aldehyde modified quaternary ammonium salt chitosan solution is 0.5-2 mg / mL.

[0019] Furthermore, the SBS substrate was made of SBS filaments with a diameter of 1.75 mm by 3D printing.

[0020] Furthermore, the 3D printer used in 3D printing was a homemade device with a nozzle temperature of 210°C and a bed temperature of 110°C.

[0021] Furthermore, the preparation method of polydopamine modified zeolite imidazolate framework-8 is:

[0022] Add 2-methylimidazole to the zinc acetate solution, then add dopamine hydrochloride, stir and react for 4 to 6 hours, centrifuge at a speed of 10000 to 14000 r / min for 10 to 15 minutes, collect and wash the solid phase product, and then dry it at 60 to 80°C.

[0023] Furthermore, the final concentration of 2-methylimidazole in the zinc acetate solution is 1-2 M; and the final concentration of dopamine hydrochloride after addition is 0.5-2 mg / mL.

[0024] Furthermore, the preparation process of polydopamine-modified hydroxyapatite is as follows:

[0025] (1) Ca(NO 3 ) 2 ·4H 2 O solution and (NH 4 ) 2 HPO 4 The solutions are mixed, the pH value is adjusted to 10, and then stirred at 70-80° C. for 4-6 hours; after the reaction is completed, the solid phase product is allowed to stand for 24 hours, collected and washed, and then filtered and freeze-dried for 20-30 hours, and then calcined at 300-400° C. for 2-5 hours, and finally screened with a 100-200 mesh sieve to obtain nano hydroxyapatite;

[0026] (2) Mix the nano-hydroxyapatite solution and the dopamine hydrochloride solution, stir for 4 to 6 hours, centrifuge at a speed of 10,000 to 14,000 r / min for 10 to 15 minutes, collect and wash the solid phase product, and then dry it at 60 to 80°C.

[0027] Furthermore, the volume ratio of the nano-hydroxyapatite solution to the dopamine hydrochloride solution is 1:1; wherein the content of nano-hydroxyapatite in the nano-hydroxyapatite solution is 10-15 mg / mL, and the content of dopamine hydrochloride in the dopamine hydrochloride solution is 10-15 mg / mL.

[0028] Furthermore, Ca(NO 3 ) 2 ·4H 2 O solution and (NH 4 ) 2 HPO 4 The concentration of the solutions was 0.5 M, and the volume ratio of the two when mixed was 1.67.

[0029] The bioactive SBS material for skull repair prepared by the above method.

[0030] The application of the above-mentioned bioactive SBS material in the preparation of skull formation material.

[0031] Beneficial effects of the present invention:

[0032] 1. The present invention adopts poly (styrene-butadiene-styrene) to prepare the base of skull repair material, which can effectively solve the problems of skull repair materials based on titanium mesh, polyetheretherester, and polymethyl methacrylate, such as high price, impact resistance, and thermal shock to the brain caused by ambient temperature.

[0033] 2. The present invention utilizes protocatechuic aldehyde-modified quaternary ammonium salt chitosan, polydopamine-modified zeolite imidazolate skeleton, and polydopamine-modified hydroxyapatite as raw materials, wherein protocatechuic aldehyde-modified quaternary ammonium salt chitosan gives the material good bactericidal properties; and polydopamine-modified zeolite imidazolate skeleton and polydopamine-modified hydroxyapatite are components that promote the material's antibacterial, bone differentiation and mineralization properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The images are of SBS, SBS-QCSC, and pHA / pZIF-8@SBS-QCSC substrates;

[0035] Figure 2 Infrared spectra of SBS, SBS-QCSC, and pHA / pZIF-8@SBS-QCSC substrates.

[0036] Figure 3This is the SEM experimental result of the antibacterial activity of the bioactive SBS material;

[0037] Figure 4 This is a graph showing the experimental results of the osteogenic differentiation ability of bioactive SBS materials. DETAILED DESCRIPTION

[0038] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.

[0039] Example 1

[0040] A method for preparing a bioactive SBS skull forming material comprises the following steps:

[0041] (1) Preparation of protocatechuic aldehyde modified quaternary ammonium salt chitosan

[0042] S1. Dissolve 5g CS in 180mL deionized water, then add 900μL acetic acid solution (0.5% v / v) and stir at 55℃ for 1h. Then add 5795μL trimethylammonium chloride glycidyl to the mixture and react at 55℃ for 18h. Centrifuge the mixture at 4500r / min for 20min, filter the supernatant, and precipitate the filtered solution in ethanol / acetone (1:1, v / v) mixed solution. Finally, dry the precipitate in a vacuum oven at room temperature for 3d to obtain QCS.

[0043] S2. Weigh 500 mg QCS and dissolve it in 40 mL MES solution (pH = 5.5), and stir overnight. Dissolve 1 g protocatechuic aldehyde in 30 mL water / methanol (2:1, v / v) mixture, and stir for 3.5 h at room temperature, then add the solution to the QCS solution. Add 250 mg NaBH 4 Slowly add it to the mixed solution until no bubbles are generated. Adjust the pH value of the solution to 5.5 and stir overnight. After the reaction is completed, put the obtained product into a dialysis bag (MWCO 3500) and dialyze it continuously in an acidic aqueous solution (pH 5.0, HCl) for 2 days, and finally freeze-dry to obtain QCSC.

[0044] (2) Preparation of polydopamine modified zeolite imidazolate framework-8

[0045] 2-Methylimidazole (2M) was added to a zinc acetate solution (0.08M) with a Tris-buffer (10mM, pH=8.5) as a solvent, and then dopamine hydrochloride was immediately added to the mixture at a final concentration of 1mg / mL, and the mixture was reacted for 4h under stirring. The obtained pZIF-8 suspension was centrifuged at a speed of 10000r / min for 10min. The obtained precipitate was then washed 3 times and dried at 60°C for 12h to obtain pZIF-8 nanoparticles.

[0046] (3) Preparation of polydopamine-modified hydroxyapatite

[0047] S1, Ca(NO 3 ) 2 ·4H 2 O solution and (NH 4 ) 2 HPO 4 The solutions were mixed at a volume ratio of 1.67 and NH 3 ·H 2 The pH value of the mixed solution was adjusted to 10, and then stirred at 70°C for 4 hours. After the reaction, the suspension was allowed to stand for 24 hours, and the obtained precipitate was washed 3 times, filtered and freeze-dried for 24 hours. The precipitate was calcined at 300°C for 2 hours and screened with a 200-mesh sieve to obtain nano-hydroxyapatite.

[0048] S2, 10mL of Tris-buffer (10mM) containing the nanohydroxyapatite (100mg) prepared above and 10mL of Tris-buffer (10mM) containing dopamine hydrochloride (100mg) were mixed and stirred for 4h to obtain pHA suspension. The suspension was centrifuged at 10000r / min for 10min, and the obtained precipitate was washed 3 times, and then dried at 60°C for 12h to obtain pHA nanoparticles.

[0049] (4) Preparation of SBS substrate

[0050] The SBS was prepared into filaments with a diameter of 1.75 mm and then processed by 3D printing. The printed product was rinsed with ethanol three times and dried at 40 °C for 2 h to obtain the 3D printed SBS substrate.

[0051] (5) Preparation of biologically active SBS materials

[0052] S1. Place an SBS substrate (21 mm × 21 mm × 1 mm) in 100 μL GPTMS and treat it with a plasma cleaner for 7 min. Rinse the treated substrate with ethanol and water alternately for 3 times to obtain an SBS-Si substrate. Dissolve QCSC in MES solution to a final concentration of 1 mg / mL. Then soak the above SBS-Si substrate in QCSC solution (pH 5.5) at 55°C for 36 h to obtain an SBS-QCSC substrate.

[0053] S2, soak the SBS-QCSC substrate in pHA suspension for 40 min, then soak it in pZIF-8 suspension for 40 min, during which the SBS-QCSC substrate was washed 3 times with Tris-buffer (10 mM). After the above steps were repeated 3 times, the substrate was rinsed for the last time to obtain the bioactive SBS cranioplasty material (pHA / pZIF-8@SBS-QCSC substrate).

[0054] Example 2

[0055] A method for preparing a bioactive SBS skull forming material comprises the following steps:

[0056] (1) Preparation of protocatechuic aldehyde modified quaternary ammonium salt chitosan

[0057] S1. Dissolve 5g CS in 180mL deionized water, then add 900μL acetic acid solution (0.5% v / v) and stir at 55℃ for 1h. Then add 5795μL trimethylammonium chloride glycidyl to the mixture and react at 55℃ for 18h. Centrifuge the mixture at 4500r / min for 20min, filter the supernatant, and precipitate the filtered solution in ethanol / acetone (1:1, v / v) mixed solution. Finally, dry the precipitate in a vacuum oven at room temperature for 3d to obtain QCS.

[0058] S2. Weigh 500 mg QCS and dissolve it in 40 mL MES solution (pH = 5.5), and stir overnight. Dissolve 1 g protocatechuic aldehyde in 30 mL water / methanol (2:1, v / v) mixture, and stir for 3.5 h at room temperature, then add the solution to the QCS solution. Add 250 mg NaBH 4 Slowly add it to the mixed solution until no bubbles are generated. Adjust the pH value of the solution to 5.5 and stir overnight. After the reaction is completed, put the obtained product into a dialysis bag (MWCO 3500) and dialyze it continuously in an acidic aqueous solution (pH 5.0, HCl) for 2 days, and finally freeze-dry to obtain QCSC.

[0059] (2) Preparation of polydopamine modified zeolite imidazolate framework-8

[0060] 2-Methylimidazole (2M) was added to a zinc acetate solution (0.08M) with a Tris-buffer (10mM, pH=8.5) as a solvent, and then dopamine hydrochloride was immediately added to the mixture at a final concentration of 0.5mg / mL, and the mixture was reacted for 4h under stirring. The obtained pZIF-8 suspension was centrifuged at a speed of 10000r / min for 10min. The obtained precipitate was then washed 3 times and dried at 60°C for 12h to obtain pZIF-8 nanoparticles.

[0061] (3) Preparation of polydopamine-modified hydroxyapatite

[0062] S1, Ca(NO 3 ) 2 ·4H 2 O solution and (NH 4 ) 2 HPO 4 The solutions were mixed at a volume ratio of 1.67 and NH 3 ·H 2 The pH value of the mixed solution was adjusted to 10, and then stirred at 70°C for 4 hours. After the reaction, the suspension was allowed to stand for 24 hours, and the obtained precipitate was washed 3 times, filtered and freeze-dried for 24 hours. The precipitate was calcined at 300°C for 2 hours and screened with a 200-mesh sieve to obtain nano-hydroxyapatite.

[0063] S2, 10mL of Tris-buffer (10mM) containing the nanohydroxyapatite (100mg) prepared above and 10mL of Tris-buffer (10mM) containing dopamine hydrochloride (150mg) were mixed and stirred for 4h to obtain pHA suspension. The suspension was centrifuged at 10000r / min for 10min, and the obtained precipitate was washed 3 times, and then dried at 60°C for 12h to obtain pHA nanoparticles.

[0064] (4) Preparation of SBS substrate

[0065] The SBS was prepared into filaments with a diameter of 1.75 mm and then processed by 3D printing. The printed product was rinsed with ethanol three times and dried at 40 °C for 2 h to obtain the 3D printed SBS substrate.

[0066] (5) Preparation of biologically active SBS materials

[0067] S1. Place an SBS substrate (21 mm × 21 mm × 1 mm) in 100 μL GPTMS and treat it with a plasma cleaner for 7 min. Rinse the treated substrate with ethanol and water alternately for 3 times to obtain an SBS-Si substrate. Dissolve QCSC in MES solution to a final concentration of 1.5 mg / mL. Then soak the above SBS-Si substrate in QCSC solution (pH 5.5) at 55°C for 36 h to obtain an SBS-QCSC substrate.

[0068] S2, soak the SBS-QCSC substrate in pHA suspension for 40 min, then soak it in pZIF-8 suspension for 40 min, during which the SBS-QCSC substrate was washed 3 times with Tris-buffer (10 mM). After the above steps were repeated 3 times, the substrate was rinsed for the last time to obtain the bioactive SBS cranioplasty material (pHA / pZIF-8@SBS-QCSC substrate).

[0069] Example 3

[0070] A method for preparing a bioactive SBS skull forming material comprises the following steps:

[0071] (1) Preparation of Perillaldehyde-modified Quaternary Ammonium Salt Chitosan

[0072] S1. Dissolve 5g CS in 180mL deionized water, then add 900μL acetic acid solution (0.5% v / v) and stir at 55℃ for 1h. Then add 5795μL trimethylammonium chloride glycidyl to the mixture and react at 55℃ for 18h. Centrifuge the mixture at 4500r / min for 20min, filter the supernatant, and precipitate the filtered solution in ethanol / acetone (1:1, v / v) mixed solution. Finally, dry the precipitate in a vacuum oven at room temperature for 3d to obtain QCS.

[0073] S2. Weigh 500 mg QCS and dissolve it in 40 mL MES solution (pH = 5.5), and stir overnight. Dissolve 1 g perillaldehyde in 30 mL water / methanol (2:1, v / v) mixture, and stir for 3.5 h at room temperature, then add the solution to the QCS solution. Add 250 mg NaBH 4 Slowly add it to the mixed solution until no bubbles are generated. Adjust the pH value of the solution to 5.5 and stir overnight. After the reaction is completed, put the obtained product into a dialysis bag (MWCO 3500) and dialyze it continuously in an acidic aqueous solution (pH 5.0, HCl) for 2 days, and finally freeze-dry to obtain QCSC.

[0074] (2) Preparation of polydopamine modified zeolite imidazolate framework-8

[0075] 2-Methylimidazole (2M) was added to a zinc acetate solution (0.08M) with a Tris-buffer (10mM, pH=8.5) as a solvent, and then dopamine hydrochloride was immediately added to the mixture at a final concentration of 1.5mg / mL, and the mixture was reacted for 4h under stirring. The obtained pZIF-8 suspension was centrifuged at a speed of 10000r / min for 10min. The obtained precipitate was then washed 3 times and dried at 60°C for 12h to obtain pZIF-8 nanoparticles.

[0076] (3) Preparation of polydopamine-modified hydroxyapatite

[0077] S1, Ca(NO 3 ) 2 ·4H 2 O solution and (NH 4 ) 2 HPO 4 The solutions were mixed at a volume ratio of 1.67 and NH 3 ·H 2 The pH value of the mixed solution was adjusted to 10, and then stirred at 70°C for 4 hours. After the reaction, the suspension was allowed to stand for 24 hours, and the obtained precipitate was washed 3 times, filtered and freeze-dried for 24 hours. The precipitate was calcined at 300°C for 2 hours and screened with a 200-mesh sieve to obtain nano-hydroxyapatite.

[0078] S2, 10mL of Tris-buffer (10mM) containing the nanohydroxyapatite (150mg) prepared above and 10mL of Tris-buffer (10mM) containing dopamine hydrochloride (100mg) were mixed and stirred for 4h to obtain pHA suspension. The suspension was centrifuged at 10000r / min for 10min, and the obtained precipitate was washed 3 times, and then dried at 60°C for 12h to obtain pHA nanoparticles.

[0079] (4) Preparation of SBS substrate

[0080] The SBS was prepared into filaments with a diameter of 1.75 mm and then processed by 3D printing. The printed product was rinsed with ethanol three times and dried at 40 °C for 2 h to obtain the 3D printed SBS substrate.

[0081] (5) Preparation of biologically active SBS materials

[0082] S1. Place an SBS substrate (21 mm × 21 mm × 1 mm) in 100 μL KH560 and treat it with a plasma cleaner for 7 min. Rinse the treated substrate with ethanol and water alternately for 3 times to obtain an SBS-Si substrate. Dissolve QCSC in MES solution to a final concentration of 1 mg / mL. Then soak the SBS-Si substrate in a QCSC solution (pH 5.5) at 55°C for 36 h to obtain an SBS-QCSC substrate.

[0083] S2, soak the SBS-QCSC substrate in pHA suspension for 40 min, then soak it in pZIF-8 suspension for 40 min, during which the SBS-QCSC substrate was washed 3 times with Tris-buffer (10 mM). After the above steps were repeated 3 times, the substrate was rinsed for the last time to obtain the bioactive SBS cranioplasty material (pHA / pZIF-8@SBS-QCSC substrate).

[0084] Experimental Example 1

[0085] The bioactive SBS material prepared in Example 1 of the present application was subjected to antibacterial testing, and the specific operation steps are as follows:

[0086] SBS, SBS-QCSC, and pHA / pZIF-8@SBS-QCSC materials (7 mm × 7 mm × 1 mm) were sterilized with 75% anhydrous ethanol and then immersed in 200 mL of bacterial suspension (2 × 10 7 CFU / mL) and cultured at 37°C for 48h. The material was then removed and washed with PBS, followed by bacterial fixation and SEM observation. The experimental results are shown in Figure 3 .

[0087] according to Figure 3 It can be seen that Pseudomonas aeruginosa and Staphylococcus aureus grow in clusters on the SBS material and form a biofilm. Compared with the SBS material, the number of bacteria on the surface of SBS-QCSC and pHA / pZIF-8@SBS-QCSC materials is significantly reduced, indicating that they have good antibacterial properties, and the antibacterial property of pHA / pZIF-8@SBS-QCSC materials is particularly significant. Compared with the current skull shaping materials, the pHA / pZIF-8@SBS-QCSC skull shaping materials prepared by the present invention have intrinsic antibacterial properties.

[0088] Experimental Example 2

[0089] The bioactive SBS material prepared in Example 1 of the present application was tested for osteogenic differentiation ability, and the specific operation steps are as follows:

[0090] SBS, SBS-QCSC, and pHA / pZIF-8@SBS-QCSC materials (7 mm × 7 mm × 1 mm) were sterilized with 75% anhydrous ethanol and then placed in a 48-well plate. MC3T3-E1 cells were further inoculated at 5 × 10 4 The cells were inoculated on the material at a density of 10 cells / well and cultured. The culture medium was a complete culture medium containing 50 μg / mL L-ascorbic acid and 10 mM β-glycerophosphate disodium hydrate, which was changed every 2 days. The cells were used after 7, 14, and 21 days of culture. Total RNA was extracted from MC3T3-E1 cells on each substrate (Thermo Fisher Scientific, USA). The extracted total RNA was then reverse transcribed using a reverse transcription system kit (Thermo Fisher Scientific, USA), and finally RT-qPCR sequencing was performed and 2 -ΔΔCt The data were processed and analyzed by the mRNA expression level. The experimental results are shown in Figure 4 .

[0091] according to Figure 4 It can be seen that compared with MC3T3-E1 cells cultured in SBS and SBS-QCSC materials, MC3T3-E1 cells cultured in pHA / pZIF-8@SBS-QCSC materials showed significantly increased expression levels of alkaline phosphatase (ALP), Runt-related transcription factor 2 (Runx2) and type I collagen (Col I). ALP, Runx2 and Col I are osteogenic differentiation-related genes. The higher the mRNA level of their expression, the stronger the osteogenic differentiation ability of the cells. This further shows that the pHA / pZIF-8@SBS-QCSC cranioplasty material prepared by the present invention has significant advantages in promoting osteogenic gene expression.

Claims

1. A method for preparing a bioactive SBS material for skull repair, characterized in that: include: Quaternary ammonium salt chitosan modified with natural aldehyde compounds is covalently linked to a poly(styrene-butadiene-styrene) SBS substrate, and then polydopamine-modified zeolite imidazolate framework-8 and polydopamine-modified hydroxyapatite are fixed on the surface; the natural aldehyde compound is protocatechuic aldehyde, vanillin or perillaldehyde; The process of covalently linking the modified quaternary ammonium salt chitosan on the SBS substrate is as follows: (1) Placing the SBS substrate in a silane coupling agent, and then cleaning after plasma surface treatment to obtain an SBS-Si substrate; (2) Place the SBS-Si substrate in a natural aldehyde-modified quaternary ammonium salt chitosan solution and soak it at 50-70°C for 30-50 hours.

2. The preparation method according to claim 1, characterized in that: The process of modifying quaternary ammonium salt chitosan with natural aldehyde compounds is as follows: After dissolving the quaternary ammonium salt chitosan, add the natural aldehyde compound solution, then add NaBH4, and adjust the pH value of the solution to 5.5, stir overnight, and then dialyze in an acidic environment for 2 to 3 days.

3. The preparation method according to claim 1, characterized in that: The preparation method of the polydopamine modified zeolite imidazolate framework-8 is: Add 2-methylimidazole to the zinc acetate solution, then add dopamine hydrochloride, stir and react for 4-6 hours, centrifuge at a speed of 10000-14000 r / min for 10-15 minutes, collect and wash the solid phase product, and then dry it at 60-80°C.

4. The preparation method according to claim 1, characterized in that: The preparation process of the polydopamine-modified hydroxyapatite is as follows: (1) A Ca(NO3)2∙4H2O solution and a (NH4)2HPO4 solution with a concentration of 0.5 M were mixed in a volume ratio of 1.67, and the pH value was adjusted to 10, and then stirred at 70-80°C for 4-6 hours; after the reaction was completed, the mixture was allowed to stand for 24 hours, and the solid phase product was collected and washed, and then filtered and freeze-dried for 20-30 hours, and then calcined at 300-400°C for 2-5 hours, and finally screened with a 100-200 mesh sieve to obtain nano-hydroxyapatite; (2) Mix the nanohydroxyapatite solution and dopamine hydrochloride solution, stir for 4 to 6 hours, and then centrifuge at a speed of 10,000 to 14,000 r / min for 10 to 15 minutes. Collect and wash the solid phase product, and then dry it at 60 to 80°C.

5. The preparation method according to claim 4, characterized in that: The volume ratio of the nano-hydroxyapatite solution to the dopamine hydrochloride solution is 1:1; wherein the content of nano-hydroxyapatite in the nano-hydroxyapatite solution is 10-15 mg / mL, and the content of dopamine hydrochloride in the dopamine hydrochloride solution is 10-15 mg / mL.

6. The bioactive SBS material for skull repair prepared by the method according to any one of claims 1 to 5.

7. Use of the bioactive SBS material for skull repair according to claim 6 in the preparation of skull formation materials.

Citation Information

Patent Citations

  • O-quaternary ammonium salt oligochitosan vanillina Schiff base bacteriostatic agent and preparation method thereof

    CN102464729A

  • Method for fabrication of synthetic bioceramic implant material based on carbonate hydroxyapatites

    EP2338531A1